KONTRIBUSI MASJID AMALBAKTI MUSLIM PANCASILA (YAMP) DALAM PEMBANGUNAN MASYARAKAT MUSLIM DI KOTA AMBON - nur khozin; Hasan Lauselang (al-Iltizam: Jurnal Pendidikan Agama Islam, 2021)
ABSTRACT A mosque is a religious institution that is inseparable from the spiritual, social and cultural life of the people. Where there are Muslims, there must be a mosque there, the mosque is also a symbol of Islam, if there is a mosque then there is allegedly a Muslim community. Mosques have a big enough role for society, not only as places of worship, but also as centers of civilization for Muslims. The results showed that the history of the YAMP Mosque in Maluku Province, there are 6 mosques. There are 4 units in Ambon City, namely 1 at the IAIN Ambon Campus, 1 at the UNPATTI Campus, 1 in Tihu/Perumnas Poka Village, and 1 at BTN Wayame. Meanwhile, one more mosque is located in Southeast Maluku Regency to be precise next to the Tual City Regional Hospital, another mosque is located in Banda Naira Tanah Rata. As well as the model of prospering the YAMP mosque by the takmir of the mosque or the surrounding community besides worship, Islamic studies are carried out, discussions and also social activities that are useful for the community and members of the YAMP mosques in Ambon city. The community's response to the YAMP mosque is very much needed because of its good existence, and it really helps the worship process as well as to get closer to God Almighty. In addition, the YAMP mosque is very well designed because in the delivery of sermons and recitations it is not obstructed by pillars in the main room so that it is clear that it is clear who delivers the sermon and / or who provides the material. The contribution of the YAMP mosque in the development of the Muslim community in Ambon city is very good, this can be seen from the routine studies carried out by both mosque administrators and religious groups, both routine studies, breaking fast together, cutting sacrificial animals, other religious discussions. in building the country in the future the better. In addition, the YAMP mosque has majlis ta'lim, TPQ, PAUD / RA and MIT. This has been around for a long time. ABSTRAK Masjid merupakan pranata keagamaan yang tidak terpisahkan dari kehidupan spiritual, sosial, dan kultural umat. Dimana ada umat Islam pasti di situ ada masjid, masjid juga merupakan simbol keislaman, jika ada masjid maka di situpun disinyalir ada masyarakat muslim. Masjid memiliki peran yang cukup besar bagi masyarakat, bukan hanya sebagai tempat ibadah, melainkan juga sebagai pusat peradaban bagi umat Islam. Hasil penelitian menunjukkan bahwa sejarah Masjid YAMP yang berada di Provinsi Maluku terdapat 6 buah masjid. Keberadaanya 4 buah di Kota Ambon yaitu 1 buah di Kampus IAIN Ambon, 1 buah di Kampus UNPATTI, 1 buah di Kelurahan Tihu/Perumnas Poka, dan 1 buah di BTN Wayame. Sedangkan 1 masjid lagi berada di Kabupaten Maluku Tenggara tepatnya di samping RSUD Kota Tual, 1 masjid lagi diberada di Banda NairaTanah Rata. Serta Model memakmurkan masjid YAMP oleh takmir masjid atau masyarakat sekitar selain ibadah, dilakukannya kajian-kajian keislaman, diskusi-diskusi dan juga kegiatan-kegiatan sosial yang berguna untuk masyarakat serta jamaah masjid masjid YAMP di kota Ambon. Tanggapan masyarakat tentang keberadaan masjid YAMP sangat dibutuhkan karena keberadaannya yang baik, dan sangat membantu proses ibadah sekaligus mendekatkan diri mereka terhadap Tuhan Yang Maha Esa. Selain itu juga masjid YAMP sangat baik desainnya karena dalam penyampaian khotbah maupun pengajian tidak dihalangi oleh tiang-tiang di ruang utama sehingga jelas kelihatan yang menyampaikan khutbah dan atau yang memberikan materi. Kontribusi masjid YAMP dalam pembangunan masyarakat Muslim di kota Ambon sangat baik hal ini bisa dilihat dari kajian-kajian rutin yang dilaksanakan baik pengurus masjid maupun majelis ta’lim baik itu kajian rutin, buka puasa bersama, memotong hewan qurban, diskusi-diskusi keagamaan yang lain dalam membangun negara kedepan semakin baik. Selain itu juga masjid YAMP memiliki majlis ta’lim, TPQ, PAUD/RA dan MIT ini sudah berjalan lama.